PARASITE DIVERSITY OF OSTEOGLOSSUM BICIRRHOSUM, AN OSTEOGLOSSIDAE FISH FROM AMAZON - Gonçalves Rodrigues, Maria de Nazaré (2014)
We investigated the ecological relationships between parasites and the host silver arowana Osteoglossum bicirrhosum Cuvier, 1829 from Amazonian basin, in Brazil. A total of 1,570.539 parasites belonging to different taxa were found including Ichthyophthirius multifiliis, Piscinoodinium pillulare (Protozoa), Gonocleithrum aruanae, Gonocleithrum planacrus, Gonocleithrum coenoideum (Monogenoidea) and Camallanus acaudatus (Nematoda); all had an aggregated dispersion. The Brillouin diversity index was 0.11 ± 0.21, evenness was 0.08 ± 0.15 and species richness was 3.2 ± 0.5. There was positive correlation between the intensity of I. multifiliis and host size, as well as between the intensity of Gonocleithrum spp. and the relative condition factor of hosts. This is the first report on parasitic diversity indices in wild O. Bicirrhosum. The parasites community was characterized by low species diversity and species richness, and by high prevalence of ectoparasites species.